Teachers’ Perceptions towards the Use of CLT in EFL Context - Almshakowi, Faiza M.; Aghnayah, Mohamed (مجلة الاصالة, 2022)
This paper aims to review the teachers' perceptions towards communicative language teaching in English language teaching settings. It also intends to discover whether EFL teachers aware of the main features of CLT or not. In order to achieve these aims, quantitative approach was used. The data was collected from 40 university teachers by using a questionnaire. The results of this study showed that the majority of English teachers could be considered as CLT followers, most of them are aware and understand the value of applying it in their classes. However, it also showed that there are some misconceptions about the goals of CLT which caused as a result of the misunderstanding of some terms of CLT. There was a small gap between teachers’ perceptions towards communicative language teaching and their practice in their classes. This gap can be overcome by providing University teachers with in-service training sessions about how to link CLT theory into the practice in ELT classes. Furthermore, the University should make some workshops about CLT to explain any misconception and to motivate instructors to use it successfully.